أثر الحوافز على الأداء الوظيفي في القطاع الصناعي: دراسة حالة مصنع سكر عسلاية للعام ۲۰۲۲. ولاية النيل الأبيض، السودان - د السماني محمد الغالي نور الدائم; د. تهاني فارس عبيد يوسف (White Nile Journal for Studies and Research, 2024)
The research problem is represented in the existence of deficiencies or weaknesses in the systems and methods of incentives applied to employees, satisfying their psychological needs and raising the morale of individuals. Achieving the following: clarifying the significant role of incentives in raising the effectiveness of performance, clarifying the relationship between job. performance and the work environment, highlighting the most prominent problems in granting incentives, the research tested the following hypotheses: There is a statistically significant relationship between motivation methods and job performance, there is a statistically significant relationship between incentive forms and job performance, there is a statistically significant relationship between the basis for granting incentives and job performance, the research came out with a number of results, the most important of which are: The factory management motivates the employees by giving them privileges that differ according to their positions. The factory management estimates the size of the incentive according to the employee's need. The employee's distance from pressure is reflected in seriousness, dedication, and his ability to assume responsibility. The research recommended recommendations, including: The factory management should seek to find motivating ways such as promotions. The factory management should motivate the employees through bonuses during the month. The factory management should choose the appropriate timing to give the incentive. The employee's knowledge of the requirements of his job should make him able to perform it efficiently.